Translation System from Arabic Text to Arabic Sign Language - Nadia Aouiti; Mohamed Jemni (Universitas Dian Nuswantoro and IndoCEISS, 2018)
This research paper presents our ongoing project aiming at translating in real time an Arabic text to Arabic Sign Language (ArSL). This project is a part of a Web application [1] based on the technology of the avatar (animation in the virtual world). The input of the system is a text in natural language. The output is a real-time and online interpretation in sign language [2]. Our work focuses on the Arabic language as the text in the input, which needs many treatments due to the particularity of this language. Our solution starts from the linguistic treatment of the Arabic sentence, passing through the definition and the generation of Arabic Annotation Gloss system and coming finally to the generation of an animated sentence using the avatar technology.